From a Love of Nature to a World of Earth Observations - Michael D. King (Perspectives of Earth and Space Scientists)
Abstract This article is a reflection on my career in Earth remote sensing and its evolution from an early childhood love of nature. I recount the influence of key people along the way to my development as an atmospheric scientist, and ultimately to my role as senior project scientist of NASA's Earth Observing System, one of the largest science program in the world in the 1990s and 2000s. Special focus is on unexpected encounters and opportunities to learn and explore, and ultimately to play a role in the remote sensing of aerosol and cloud properties from the ground, aircraft, and satellites. A major focus of much of my research at NASA Goddard Space Flight Center was on the development and exploitation of the Moderate Resolution Imaging Spectroradiometer that ultimately flew on NASA's Terra and Aqua satellites. As a participant on this science team, I had the opportunity to learn from and collaborate with biological oceanographers, atmospheric scientists, and terrestrial ecologists, and ultimately to publish in each of these areas, far more than my basic academic “home.”